Mesenteric lymphangioma mimicking a cystic ovarian mass on imaging. (1st February 2016) - Hitzerd, Emilie; van Hamont, Dennis; Pijnenborg, Johanna M A
Abstract : Pelvic cystic masses are frequently observed in women. Most lesions are benign and of ovarian origin. However, non-ovarian lesions can be easily confused with cystic ovarian masses on imaging, which hampers diagnostic and therapeutic management. In this report, a rare case of mesenteric lymphangioma mimicking an ovarian cystic mass, discovered as an incidental finding on orthopaedic MRI in an adult female, is presented. The report highlights the sometimes difficult diagnostic process of pelvic cystic masses, due to an extensive differential diagnosis and the fact that imaging is often inconclusive. Even though most cystic masses are of ovarian origin, non-ovarian causes can mimic ovarian masses and should be considered as differential diagnoses. Surgical exploration may be necessary to exclude malignant causes.